History of International Relations at a Glance - Marsili, M. (Ciência 2020, 2020)
History of International Relations at a Glance: 1) Westphalian Sovereignty Result of: Thirty Year’s War (1618-1648) Catholic states v. Protestant states in western and central Europe Based on: Peace of Westphalia (Treaties of Osnabruck and Munster). 2) Concert of Europe (Vienna System) Result of: Napoleonic Wars (1799-1815). Based on: Congress of Vienna (1815). 3) Versailles-Washington System Result of: World War I (1914-1918). Based on: Peace Treaty of Versailles (1919) and Washington Naval Conference (1921-1922). 4) Yalta-Potsdam World Order Result of: World War II (1939-1945). Based on: Yalta Conference (February 1945) and Potsdam Conference (July-August 1945). 5) Modern System of International Relations Result of: Cold War’s end and dissolution of USSR and Warsaw Pact (1991).